Beyond the hype: Evaluating the impact of generative AI on brand authenticity, image, and consumer behavior in the restaurant industry - Ali, Laiba; Ali, Faizan; Abdalla, Moh'd Juma; Alotaibi, Salman (Elsevier Sci Ltd, 2025)
Grounded in the Stimulus-Organism-Response (S-O-R) framework, this study investigates the impact of Generative Artificial Intelligence (GenAI) adoption on brand authenticity, brand image, and self-brand congruity and their subsequent effects on consumer behavior, including electronic word-of-mouth (e-WOM) and behavioral intention, within the restaurant industry. A scenario-based experimental design was employed, presenting participants with hypothetical situations of restaurants utilizing AI-generated and human-created social media content. MANOVA results revealed that perceived brand authenticity, image, and self-brand congruity were significantly lower in the GenAI condition compared to the human-generated content condition. Multigroup analysis further indicated that while brand authenticity and image had diminished effects on consumer behavior under the GenAI condition, self-brand congruity played a significantly stronger role in driving e-WOM and behavioral intentions. These findings suggest that AI-generated content may weaken traditional brand perception cues, prompting consumers to rely more on internal identity alignment. The study contributes to S-O-R theory by demonstrating how content source (AI vs. human) moderates the pathways from brand perception to behavior and provides actionable guidance for hospitality marketers seeking to balance GenAI integration with consumer expectations for authenticity and personal resonance.
Keywords: Brand authenticity; Brand image; E-WOM; Generative artificial intelligence; Behavioral intention and self-brand congruity